Deviations : designing architecture: a manual. - Angélil, Marc M., 1954-; Hebel, Dirk, ....- (Bazel : Birkhäuser, 2008)
DEVIATIONS, a handbook and users' guide on architectural design pedagogy, pursues the strategy of the Trojan horse, infiltrating a given system's practices in order to transform them from within. While documenting the opening moves of the architectural design curriculum at the ETH Zurich, the manual exposes teaching to a series of tests. It promotes a departure from the seemingly familiar and stable grounds of recognized design approaches in pursuit of more open tactics - initiating a plea for a new type of architectural practice. Rather than opposing the established order of things, the approach embraces this order while simultaneously working both with and against manufactured conventions. Taking on the operative mechanisms of everyday practice, median standards, and normative action as the very stuff of design, concepts and techniques emerge whose foci are not based on form, but on how architecture might perform. In addition to the orientation provided within the individual chapters, a graphic navigational structure guides readers through the book as a whole and enables them to scan through the work or focus on specific projects. Following the framework of an academic year, the book is divided into a series of sections devoted to the thematic areas: space, program, technology, context and form.
Keywords: Architectural design -- Study and teaching (Higher) -- Handbooks, manuals, etc